The history manifesto - Guldi, Jo (Joanna), 1978-; Armitage, David, 1965- (Cambridge University Press, 2014)
How should historians speak truth to power - and why does it matter? Why is five hundred years better than five months or five years as a planning horizon? And why is history - especially long-term history - so essential to understanding the multiple pasts which gave rise to our conflicted present? The History Manifesto is a call to arms to historians and everyone interested in the role of history in contemporary society. Leading historians Jo Guldi and David Armitage identify a recent shift back to longer-term narratives, following many decades of increasing specialisation, which they argue is vital for the future of historical scholarship and how it is communicated. This provocative and thoughtful book makes an important intervention in the debate about the role of history and the humanities in a digital age. It will provoke discussion among policymakers, activists and entrepreneurs as well as ordinary listeners, viewers, readers, students and teachers. This title is also available as Open Access.